Dental management of cutaneous fistula ar mandible et causa pulp necrose 46 in a pediatric patient with suspected ADHD: A Case Report - Inayah, Yayah; Harmawaty, Harmawaty (Journal of Case Reports in Dental Medicine, 2024)
Objective: The purpose of this paper is to report the success of root canal treatment (PSA) on the mandibular right first molar for the management of periapical abscess accompanied by cutaneous fistula ar mandible. Methods: This case report describes the management of dental abscess submandibular dextra et causa pulp necrosis of tooth 46 with root canal treatment of tooth 46. Emergency management of dental abscess submandibular dextra et causa pulp necrosis of tooth 46 was carried out with root canal treatment accompanied by the administration of antibiotics.Results: Pulp necrosis can be caused by various noxious irritant injuries to the pulp. Irritation to the pulp or periradicular tissues can cause inflammation. Microbial/Bacterial is the most common cause of inflammation. Microorganisms found in dental caries are the main source of irritation to the pulp and periradicular tissues. Microorganisms in caries produce 4 toxins that can penetrate the pulp through the dentinal tubules. This initial response results in a focal accumulation of chronic inflammatory cells such as macrophages, lymphocytes and plasma cells. Conclusion: There was no active swelling in the patient so it was indicated for root canal treatment.